2021
DOI: 10.4049/jimmunol.2000490
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in Macrophage Responses to Obesity-Mediated Changes Determine Migratory and Inflammatory Traits

Abstract: The mechanisms whereby obesity differentially affects males and females are unclear. Because macrophages are functionally the most important cells in obesity-induced inflammation, we sought to determine reasons for male-specific propensity in macrophage migration. We previously determined that male mice fed a high-fat diet exhibit macrophage infiltration into the hypothalamus, whereas females were protected irrespective of ovarian estrogen, in this study, we show that males accumulate more macrophages in adipo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
46
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(67 citation statements)
references
References 88 publications
8
46
0
Order By: Relevance
“…Our migration studies with monocytes are consistent with others showing male monocyte-derived macrophages to migrate readily to fatty acid exposure whereas female macrophages have dampened migration ( 39 ). While the literature is controversial about the importance of MCP1 in obesity-induced inflammation ( 47 , 48 ), using the chemokine and PA treatment, we identified that male monocytes specifically have a more robust trafficking response in vitro.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our migration studies with monocytes are consistent with others showing male monocyte-derived macrophages to migrate readily to fatty acid exposure whereas female macrophages have dampened migration ( 39 ). While the literature is controversial about the importance of MCP1 in obesity-induced inflammation ( 47 , 48 ), using the chemokine and PA treatment, we identified that male monocytes specifically have a more robust trafficking response in vitro.…”
Section: Discussionsupporting
confidence: 92%
“…Chemokines and their receptors are noted to have significant redundancy ( 38 ), but an understanding of differences by sex with diet is helpful for understanding the dimorphism ( 39 ). Among the top differentially expressed genes in pathways associated with cell adhesion, migration, and interaction, we looked at markers for pro-inflammatory states of ATMs in heatmaps.…”
Section: Resultsmentioning
confidence: 99%
“…The decrease in estrogen levels in menopausal women is associated with the loss of subcutaneous fat and the abdominal fat accumulation ( Lizcano and Guzmán, 2014 ). In support of estrogen importance, increased adiposity after oophorectomy and ovarian estrogen clearance were observed in rodents and monkeys ( Chen et al, 2021 ). In the case of men, low testosterone levels have also been proposed as a risk factor for pathophysiology, including insulin sensitivity and DM2 ( Terrazas et al, 2019 ).…”
Section: Chronic Obesity and Neuroinflammationmentioning
confidence: 94%
“…There is a differential response in adiposity and the prevalence of obesity-associated diseases between males and females, particularly in mammals. In obese men, the occurrence of heart disease and myocardial infarction is higher, while in women, obesity is associated with ischemic stroke ( Chen et al, 2021 ). When comparing men and women with the same BMI, it has been observed that women have a 10% higher body fat content.…”
Section: Chronic Obesity and Neuroinflammationmentioning
confidence: 99%
“…Furthermore, gender-specific associations of gene polymorphisms with disease susceptibility have been found in MS patients [ 44 ]. In addition, cellular responses to adipokines might differ between gender, since more and more cell types are being discovered of which their function and phenotype is dictated by gender [ 120 , 121 , 122 ].…”
Section: Adipokines Inflammation and Msmentioning
confidence: 99%